Pengaruh Campuran Abu Sekam Padi terhadap Kuat Tekan Paving Block - Budi Waluyo; As'at Pujianto; Bagus Soebandono (Semesta Teknika, 2013)
Rice husk is an abundant by-product of rice milling results, and so far only used as a fuel for combustion red stones, burning for cooking or thrown away. Rice husk ash (RHA) is a waste material of rice that has special properties. This material also contains chemical compounds that can be pozzolan, which contains silica (SiO2), a compound which, when mixed with cement and water can be used to enhance the compressive strength and tensile strength of concrete while silica is a chemical compound that is dominant in the rice husk ash. This study aimed to compare the results of the average compressive strength of the normal paving block with the added ingredient of rice husk ash, assess the effect of the addition of rice husk ash to the compressive strength and prices comparison between the paving block and normal paving block with the added ingredient of rice husk ash. In this study, rice husk ash serves as a replacement for cement additives with a variation of 0%, 30%, 35% and 40% by weight of cement in comparison 1pc: 10ps, 1pc: 13ps and 1pc: 15ps. The results showed that the paving blocks with a mixture of rice husk ash in comparison 1pc: 10ps produce optimum compressive strength with a mixture of rice husk ash 16.6% in the amount of 32.709 MPa. Furthermore in comparison 1pc: 13ps, paving block compressive strength values obtained with the optimal mix of rice husk ash rice 13.0% amounting to 23.709 MPa. Finally, in comparison 1pc: 15ps, paving block compressive strength values obtained with the optimal mix of rice husk ash 15.0% amounting to 17.260 MPa.